For an introduction to the congress. The court of words: the dialogue between rhetoric and law between the republican and imperial ages - Balbo, Andrea (Ciceroniana On Line, 2022)
The conference Da Cicerone al Digesto: interazioni fra oratoria giudiziaria, retorica e diritto tra l'età repubblicana e imperiale, held in Turin on 22-23 November 2021 in the premises of Palazzo Nuovo in via S. Ottavio 20, had both symbolic and scientific value.